K-Pop-Based Strategies to Increase Teens' Learning Motivation - Ridlo, Wildani; Na’imah, Na’imah; Agustina, Reni; Adawiyah, Miftahul (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This research aims to explore the synergy between learning and the positive impact of K-Pop in increasing the interest and learning outcomes of Indonesian teenagers, as well as analyzing strategies to improve teenagers' learning motivation through K-Pop popular culture. This research is a qualitative case study type with primary data collected through interviews and questionnaires as well as secondary data from related literature. The analysis technique used is data condensation. previous research used a qualitative descriptive approach. K-Pop provides socialization and space for self-expression for teenagers and creates strong communities. Teenagers seek an outlet from pressure through K-Pop. Visual, auditory, and kinesthetic learning methods integrated with religious understanding can maximize understanding, provide inspiration and motivation, and form a psychological approach to students' emotional and spiritual needs. This strategy can create a conducive learning environment to support student development. However, this research is limited to learning motivation strategies for teenage K-Pop fans, while the effectiveness of strategies on academic achievement results needs to be tested empirically through experimental studies.